Answer:
a^2 + 2ab + b^2 - c^2
Step-by-step explanation:
When you multiply all the terms together you get a^2 + ab + ac + ab + b^2 + bc - ac - bc - c^2. Then you can just combine like terms and simplify it to a^2 + 2ab + b^2 - c^2. Hope this helps :)
Answer:
23
Step-by-step explanation:
they add five
9+5=14
12+5=17
15+5=20
18+5=23
Sorry but this isnt even a full question.......
97% is greater than 0.097
Answer: Not sure
Step-by-step explanation: A is wrong because they are parallel in one is on the top to the right and 1 is on the bottom. sorry thats all i know :(